Fore/aft dynamics and performance in slalom - Tjørhom, H.; Reid, R.; Moger, T.; Haugen, P.; Gilgien, M.; Kipp, R.; Smith, G. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: While relative fore/aft motion between the skier and skis along the ski's longitudinal axis is a commonly acknowledged element of alpine skiing technique, there are differing opinions as to how much movement occurs and how important it is for performance. Although there exist numerous qualitative descriptions, few quantitative analyses of fore/aft dynamics have been published. The aim of this study was to quantify the fore/aft dynamics of a group of highly-skilled athletes in slalom and to relate these measures to performance.